To solve the equation \( 2(x + 8) = 2x + 8 \), we will use the distributive property and then simplify. Let's go step by step.
Step 1: Apply the Distributive Property
We start with the equation:
\[ 2(x + 8) = 2x + 8 \]
Using the distributive property, we distribute \(2\) to both \(x\) and \(8\):
\[ 2 \cdot x + 2 \cdot 8 = 2x + 8 \]
This simplifies to:
\[ 2x + 16 = 2x + 8 \]
Step 2: Subtract \(2x\) from both sides
Next, we will isolate the constant terms by subtracting \(2x\) from both sides:
\[ 2x + 16 - 2x = 2x + 8 - 2x \]
This simplifies to:
\[ 16 = 8 \]
Conclusion
The equation \(16 = 8\) is a false statement, meaning that there are no values of \(x\) that satisfy the equation.
Therefore, there are no solutions to the equation \(2(x + 8) = 2x + 8\).